A quarter century of mortgage risk - Stephen D. Oliner; Morris A. Davis; Will Larson (American Enterprise Institute (AEI), 2022)
This paper provides a comprehensive account of the evolution of default risk for newly originated home purchase loans since 1990. We bring together several data sources to produce this history, including loan-level data for the entire GSE book. We use these data to track a large number of loan characteristics and a summary measure of risk, the stressed default rate. Among the many results in the paper, we show that mortgage risk had already risen in the 1990s, planting the seeds of the financial crisis well before the actual event. Our results also cast doubt on explanations of the crisis that focus on low-credit-score borrowers.
Keywords: A; 330; GSEs (Fannie Mae and Freddie Mac); mortgage; Federal Housing Administration (FHA); 2008 financial crisis; Department of Veterans Affairs (VA); Housing Center: Research; Housing Center: Mortgage Risk Index